STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN BUDAYA KEAGAMAAN SISWA SEKOLAH MENENGAH PERTAMA SWASTA PERGURUANISLAM AN-NIZAM MEDAN - Irsahwandi, Muhammad (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
This research is a qualitative research. Data obtained through observation, interviews and documentation. All data collected is then analyzed using data consisting of the stages of sorting out the main data, presenting data and drawing conclusions from the evaluation. The results of the study show that: (1) the vision and mission of the school principal in developing Islamic culture are: vision, carrying out educational development in the academic and non-academic fields by upholding Islamic values and prioritizing morality. while the mission, favoring non-academic achievements of students through habituation of Islamic activities. It refers to the vision of An-Nizam Medan Private Middle School. (2) the principal's leadership style in developing Islamic culture adheres to a democratic leadership style (the principal gives uswah khasanah, likes to accept suggestions, motivates subordinates, and is firm in leading). (3) the principal's efforts in developing Islamic culture are to familiarize school values, develop curriculum, create a conducive learning environment, utilize facilities and infrastructure by maximizing school layout, apply disciplinary attitudes and Islamic Values for the ongoing Islamic culture of the school.